STEM EDUCATION AND EFFECTS OF THE STUDENTS' PERCEPTION - Drougas, Vasileios Ag.; Bin-Tahir, Saidna Zulfiqar (Uniqbu Journal of Social Sciences, 2022)
In recent years there has been a significant change in the learning areas of technology courses and those of the sciences. The introduction of STEM courses in the school at all levels has greatly helped young students to understand the essence and practice of science. An important point in this change was the participation of students in such STEM programs which changed the data in education worldwide. Although the introduction of STEM has become major for the empowerment of students and their shift to science, it is now a very important tool in the hands of teachers to create studies and presentations with their students in many different subjects, even in theoretical lessons. This has important implications for children's abilities in the learning process, in the approach to scientific fields and in the field of Physiology. In the present research, the results of the implementation of STEM programs in schools are studied and analyzed in relation to the improvement of the parameters of students' perception.